Based on Multi-Factors Grey Prediction Control for Elevator Velocity Modulation - Ye Fei; Jin Ning; Jiming Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
This paper uses the double-factors grey prediction and the fuzzy controller for the elevator car speed control. We introduce double-factors grey control to predict car vibration for elevator speed during the operation. Simulation results show that based on multi-factors gray prediction fuzzy PI control for elevator velocity modulation system closer than simple gray fuzzy PI control elevator speed control system to the actual operation. The control effect of double factors grey fuzzy PI control elevator speed control system is also satisfactory. This paper uses the double-factors grey prediction and the fuzzy controller for the elevator car speed control. We exploit the merit of which not depend on the object model and strong robustness to overcome elevator PMSM parameters drift and nonlinear effects. And we introduce double-factors grey control to predict car vibration for elevator speed during the operation. Simulation results show that based on multi-factors gray prediction fuzzy PI control for elevator velocity modulation system closer than simple gray fuzzy PI control elevator speed control system to the actual operation. The control effect of double factors grey fuzzy PI control elevator speed control system is also satisfactory. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1408